Saffron supplements modulate serum pro-oxidant-antioxidant balance in patients with metabolic syndrome: A randomized, placebo-controlled clinical trial - Tayyebeh Kermani; Seyyed Hadi Mousavi; Maryam Shemshian; Abdolreza Norouzy; Mohsen Mazidi; Atefeh Moezzi; Toktam Moghiman; Majid Ghayour-Mobarhan; Gordon. A. Ferns (Mashhad University of Medical Sciences, 2015)
Objectives: We have investigated the effect of a saffron supplement, given at a dose of 100 mg/kg, on prooxidant-antioxidant balance (PAB) in individuals with metabolic syndrome. Materials and Methods: A randomized, placebo-controlled trial design was used in 75 subjects with metabolic syndrome who were randomly allocated to one of two study groups: (1) the case group received 100mg/kg saffron and (2) the placebo control group received placebo for 12 weeks. The serum PAB assay was applied to all subjects before (week 0) and after (weeks 6 and 12) the intervention. Results: There was a significant (p=0.035) reduction in serum PAB between week 0 to week 6 and also from week 0 to week 12.  Conclusion: Saffron supplements can modulate serum PAB in subjects with metabolic syndrome, implying an improvement in some aspects of oxidative stress or antioxidant protection.